Cinema Today - ELENA OUMANO (Rutgers University Press, 2010)
When the far-fl ung bits and pieces borrowed from older, more established arts are shaped into a smooth, composite whole to make great cinema, something entirely new, powerful, and exciting results—moving images and sounds that follow their own rules of movement, space, and story to reveal a livelier, more passionately intense refl ection of the world as we experience it. This metamorphosis begs the perennial question, what is cinema? Famously posed by seminal French fi lm theorist André Bazin, the question has never been answered to everyone’s complete satisfaction, so we continue to explore it today, even while recognizing that cinema’s unique magic eludes description through mere words and that it may not always be wise to deconstruct the illusion. Yet, when thirty-nine international fi lmmakers share various and sometimes oppositional views on their art, perhaps we can piece together their ideas and approach a more comprehensive understanding of what cinema can be and how it can work. After all, who is better qualifi ed than fi lmmakers themselves to describe cinema’s collision of various art forms, textures, images, sounds, rhythms, and other expressive elements, as well as to dissect the frustrating, exhausting, and exhilarating process by which a fi lmmaker’s vision fi nds its way onto the screen? The usual way we receive information about an art from its makers is via the interview’s choppy question-and-answer format. But reading an interview can be tedious, and plowing through a collection of interviews in which the same topics, issues, and questions are directed to each subject in turn, over and over, can be even worse, like being trapped in a revolving door. Cinema Today attempts to spring the catch on that revolving door with a symposium-in-print format created by editing my interviews with thirty-nine independent and personal fi lmmakers. My questions have been removed and their answers grouped together under the various key cinema topics that form this book’s chapters